Leachate treatment through Fenton reaction-aided-chemical treatment - Thong, Hui Shan (2022)

(untitled)
As landfill leachate consists a lot of hazardous compounds that will contaminate the water nearby, leachate treatment must be carried out in order to prevent water pollution and other health problems. There are several techniques developed can be used for leachate treatment, while the Fenton reaction using heterogeneous iron oxide catalyst can conquer the shortcomings of conventional homogeneous Fenton reaction. Therefore, this project is to investigate the performance of leachate treatment using heterogeneous Fenton reaction under different conditions and parameters, i.e. the presence of light, the presence of hydrogen peroxide, the size of iron oxide particles as well as the iron oxide concentration. The effect of other parameters such as pH, reaction time, hydrogen peroxide concentration was studied prior to the experiment. The optimal pH, reaction time and hydrogen peroxide concentration that are used in this study is pH 3.0, 120 minutes and 3 g/L respectively. The results indicated that the optimal conditions and parameters is nano-sized iron oxide particles at concentration of 150 mg/L in the presence of light and hydrogen peroxide. The opacity and COD removal efficiency is reported as 25.4% and 72.3% respectively. Other than that, the reaction kinetics of Fenton reaction was also studied and results show that second-order kinetic model could explain the data very well with a